Malaria in indigenous of Lower Caura. Sucre and Cedeño municipalities, Bolívar State, Venezuela (Revista Venezolana de Salud Pública, 2019)
Malaria is a hemoparasitosis caused by intracellular protozoa belonging to the genus Plasmodium and transmitted by the bite of femalemosquitoes of the genus Anopheles . A descriptive, cross-sectional study was carried out in the indigenous communities of Bajo Caura,Sucre and Cedeño municipalities, Bolívar state, Venezuela, during the 2015-2016 period. The sample consisted of 244 inhabitants ofthe communities under study. An epidemiological survey was applied to each participant and a blood sample was taken by capillarypuncture, with prior consent and informed settlement. The diagnosis was made by direct parasitological methods of thick blood smearand smear. To relate the presence of malaria and epidemiological variables, the chi-square independence test was applied. Theobserved frequency was 7.0%, all detected cases belong to the Sucre municipality. Female people younger than 10 years of age weremore vulnerable to infection. The species Plasmodium falciparum and Plasmodium vivax were identified, the latter being the mostprevalent. The variables fever, symptomatology associated with malaria, degree of knowledge of the disease and type of housing, wereassociated with infection by Plasmodium spp. Under the conditions of this study it is concluded that, in spite of the results found in theindigenous communities, there is a focus of active malaria transmission. Finally, the information obtained represents a contribution atthe moment of making decisions regarding the components such as surveillance, control and health promotion around malaria.
Keywords: Malaria; Plasmodium; indigenous